Justyna Miecznikowska, Europeizacja partii i systemu partyjnego Austrii, Oficyna Wydawnicza ASPRA-JR, Warszawa 2018, s. 493. - Romejko, Adam (Studia Gdańskie, 2019)
Justyna Miecznikowska, Europeizacja partii i systemu partyjnego Austrii, Oficyna Wydawnicza ASPRA-JR, Warszawa 2018, s. 493.